NetBAN, a concept of network of BANs for cooperative communication: energy awareness routing solution. (2018) - Manirabona, Audace; Boudjit, Saadi; Fourati, Lamia Chaari
In this paper, a NetBAN which is a concept of network of body area networks (BANs) or wireless body area networks (WBANs) is introduced and a routing solution intending to help a group of WBANs to cooperate for relaying packets according to the energy consumption rate and the communication link quality is proposed. The main goal is to provide to the sensors a technique that helps them deliver their data even when the coordinator's battery is very low or empty or else the connection to the access point is lost, what leads to balancing energy consumption between cooperating coordinators. For this purpose, an energy threshold-based technique is used and energy-aware optimised link state routing (EA-OLSR) is defined and used. Simulation results show interesting performances in terms of network lifetime with a gain of about 30% and data delivery about 20%.